Rapid and sensitive multiplex single-tube nested PCR for the identification of five human Plasmodium species. Issue 3 (June 2018) - Saito, Takahiro; Kikuchi, Aoi; Kaneko, Akira; Isozumi, Rie; Teramoto, Isao; Kimura, Masatsugu; Hirasawa, Noriyasu; Hiratsuka, Masahiro
Abstract: Malaria is caused by five species of Plasmodium in humans. Microscopy is currently used for pathogen detection, requiring considerable training and technical expertise as the parasites are often difficult to differentiate morphologically. Rapid diagnostic tests are as reliable as microscopy and offer faster diagnoses but possess lower detection limits and are incapable of distinguishing among the parasitic species. To improve global health efforts towards malaria control, a rapid, sensitive, species-specific, and economically viable diagnostic method is needed. In this study, we designed a malaria diagnostic method involving a multiplex single-tube nested PCR targeting Plasmodium mitochondrial cytochrome c oxidase III and single-stranded tag hybridization chromatographic printed-array strip. The detection sensitivity was found to be at least 40 times higher than that of agarose gel electrophoresis with ethidium bromide. This system also enables the identification of both single- and mixed-species malaria infections. The assay was validated with 152 Kenyan samples; using nested PCR as the standard, the assay's sensitivity and specificity were 88.7% and 100.0%, respectively. The turnaround time required, from PCR preparation to signal detection, is 90 min. Our method should improve the diagnostic speed, treatment efficacy, and control of malaria, in addition to facilitating surveillance within global malaria eradication programs. Graphical abstract: Highlights: A rapid, sensitive method for diagnosis of malaria was developed. A multiplex single-tube nested PCR was used for species-specific amplification. A single-stranded tag hybridization printed-array strip was used for visualization. The assay exhibited a sensitivity and specificity of 88.7% and 100.0%, respectively. The turnaround time required, from PCR preparation to signal detection, is 90 min.